When Randomization in Collective Tournaments is Profitable for the Principal - Stefanie Aniela Lehmann (University of Bonn, Bonn Graduate School of Economics (BGSE), 2008)
In the context of principal-agent theory risk is largely seen as a source that causes inefficiencies and lowers incentives and accordingly is not in the principal's interest. In this paper I compare two different designs of a collective tournament where output in a team is generated through a particular two-stage production process. I show within a theoretical tournament framework that risk in terms of chance is beneficial from the point of view of a profit maximizing principal who organizes the tournament. Selecting an agent randomly that has to work at the final stage after all agents exerted effort at the first stage helps the principal to overcome a trade-off in incentive provision he faces when selecting the agent who works at the final stage before the tournament starts. This trade-off causes optimal efforts to be lower in a tournament without random selection compared to a tournament with random selection. As the higher efforts overcompensate additional wage costs the principal earns higher expected profits when selecting the agent that has to work at the second stage randomly after the first stage.
Keywords: D2; J3; M5; 330; collective tournament; incentives; randomization; risk; Gruppenarbeit; Extensives Spiel; Agency Theory; Risiko; Leistungsmotivation; Theorie